Sociology of Religious Moderation Literacy in MTs Student Organizations: A Study of Leadership, Conflict, and Value Negotiation - Felicia Najwa; Muh. Hanif (Kawakib: Journal of Multidisciplinary Research, 2026)
This research aims to explore the understanding of religious moderation within student organizations at MTs through a sociological lens, emphasizing aspects of leadership, dispute resolution, and value discussions. Student organizations play a crucial role in shaping character, promoting tolerance, and enhancing students' appreciation of diversity in the schooling context. The study uses a qualitative framework with a case study technique. Information was gathered via observations, interviews, and documentation involving both leaders and participants of student organizations at MTs. Findings indicate that leadership behaviors reflecting religious moderation literacy emphasize discussion, respect for others, and collaboration among members. Disputes in the organization typically stem from varying viewpoints, backgrounds, and levels of religious comprehension, yet they can be addressed through conversation and open discussions about values. Additionally, the negotiation of values is vital for fostering an inclusive, tolerant, and cohesive organizational culture. This research demonstrates that MTs student organizations play a significant role in promoting the principles of religious moderation and enhancing social bonds among students.